2012
DOI: 10.7441/joc.2012.01.11
|View full text |Cite
|
Sign up to set email alerts
|

Market Power in the Czech Banking Sector

Abstract: This paper estimates the market power in the Czech banking sector during the period 2000 2010. In order to measure the degree of market power in the Czech banking sector, the authors used the Lerner index, the Herfindahl-Hirschman index and the concentration ratio. The Lerner index is applied to data from 15 banks, which covers about 90% of the Czech banking market. The paper describes the theoretical framework of the competition, especially the Lerner index and measures of concentration. Authors also compute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The Lerner index better reflects monopoly power. For example, Repkova (2012) estimated the market power in the Czech banking industry between 2000 and 2010. He found that HHI showed a trend of modest decrease, indicating that market concentration changed appreciably over the sample period.…”
Section: Data and Research Modelmentioning
confidence: 99%
“…The Lerner index better reflects monopoly power. For example, Repkova (2012) estimated the market power in the Czech banking industry between 2000 and 2010. He found that HHI showed a trend of modest decrease, indicating that market concentration changed appreciably over the sample period.…”
Section: Data and Research Modelmentioning
confidence: 99%
“…Not only that the Lerner index can measure the market power of individual firms or specific products, but it can also measure the market power of the whole industry or market. As a result, it is considered as the only available measure of competition at the bank level (Berger, Klapper, & Turk-Ariss, 2009;Coccorese, 2009;Repkova, 2012).…”
Section: Data Descriptionsmentioning
confidence: 99%
“…Overall, the level of competition of the European banks increased over the past decade. Repkova (2012) studied the competitiveness of the Czech banking system during the 2000-2010 period. In order to measure the level of competition, the author used the Lerner index, HHI index, and the CR index.…”
Section: Literature Reviewmentioning
confidence: 99%